2010
DOI: 10.1002/chem.200902071
|View full text |Cite
|
Sign up to set email alerts
|

σ‐Alkylpalladium Intermediates in Intramolecular Heck Reactions:Isolation and Catalytic Activity

Abstract: The isolation of sigma-alkylpalladium Heck intermediates, possible when beta-hydride elimination is inhibited, is a rather rare event. Performing intramolecular Heck reactions on N-allyl-2-halobenzylamines in the presence of [Pd(PPh(3))(4)], we isolated and characterized a series of stable bridged palladacycles containing an iodine or bromine atom on the palladium atom. Indolyl substrates were also tested for isolation of the corresponding complexes. X-ray crystallographic analysis of one of the indolyl deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Foley and co‐workers synthesized an N,C‐bidentate carbene ligand that gave full conversion in the reaction of iodobenzene with butyl acrylate at a loading of 10 mol ppm . A third N,C‐bidentate carbene ligand synthesized by Broggini and co‐workers permitted a decrease in the catalyst loading to 10 mol ppm during an optimization study; however, once more the scope of the reaction was examined at catalyst loadings of 0.1‐1 mol%. The Xiao group described the use of an N,C,N‐tridentate carbene ligand in a Heck reaction; during their examination of the scope of the reaction of aryl iodides, the catalyst loading was decreased to 1 mol ppm, and this afforded 78% conversion.…”
Section: Mizoroki–heck Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Foley and co‐workers synthesized an N,C‐bidentate carbene ligand that gave full conversion in the reaction of iodobenzene with butyl acrylate at a loading of 10 mol ppm . A third N,C‐bidentate carbene ligand synthesized by Broggini and co‐workers permitted a decrease in the catalyst loading to 10 mol ppm during an optimization study; however, once more the scope of the reaction was examined at catalyst loadings of 0.1‐1 mol%. The Xiao group described the use of an N,C,N‐tridentate carbene ligand in a Heck reaction; during their examination of the scope of the reaction of aryl iodides, the catalyst loading was decreased to 1 mol ppm, and this afforded 78% conversion.…”
Section: Mizoroki–heck Couplingmentioning
confidence: 99%
“…The Stille reaction, for which four publications report a mol ppm catalyst loading, is the second most studied cross‐coupling reaction. The Broggini group reported that an N,C‐bidentate ligand formed a palladacycle that was sufficiently active to promote 7 Stille reactions at a catalyst loading of 100 mol ppm . The reaction was performed without a base in DMF at 80 °C for 24 hours, and 11 examples were presented.…”
Section: Other Cross‐coupling Reactionsmentioning
confidence: 99%
“…Further experiments (entries 4–9) allowed us to identify satisfactory conditions (entry 9). Several failed optimization attempts provided circumstantial evidence indicating the lack of involvement of a Pd 0 ‐species as the active catalyst, differing from a straightforward Heck reaction 7c. For example, the reaction failed completely when conducted in an ionic liquid solvent [entries 10 and 11, IL‐109 = trihexyl(tetradecyl)phosphonium bistriflimide], a media known to be highly effective in Pd 0 ‐mediated amination6b and Heck processes 6e.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Further experimentation revealed that the use of Pd(OAc) 2 instead of [Pd 2 (dba) 3 ] provided higher yields. For this reason, we carried out a study of the influence of different amounts of water, which revealed that the coupling reaction could be best accomplished in the presence of 5 equivalents of water.…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, the allyl amine 17 a was obtained in an acceptable 65 % yield (Scheme 5). [13] Further experimentation revealed that the use of Pd(OAc) 2 instead of [Pd 2 (dba) 3 ] provided higher yields. Employing this methodology, a variety of chiral N-Bocprotected allyl amines 17 were prepared from tosylhydrazone 16 (Scheme 6).…”
Section: Methodsmentioning
confidence: 99%